Instituting a program to reduce the erythrocyte transfusion rate was accompanied by reductions in the incidence of bronchopulmonary dysplasia, retinopathy of prematurity and necrotizing enterocolitis. (19th September 2013) - Del Vecchio, Antonio; Henry, Erick; D'Amato, Gabriele; Cannuscio, Annamaria; Corriero, Luigi; Motta, Mario; Christensen, Robert D.
Abstract: Bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), and necrotizing enterocolitis (NEC) all likely involve oxidative damage to immature tissues. It has been postulated that transfusions of adult erythrocytes contribute to the risk of developing these morbidities, as a consequence of adult hemoglobin releasing non-physiological quantities of O2 to developing tissues. In 2009, we instituted a concerted effort to diminish erythrocyte transfusions in our NICU, and in 2013 we performed a before vs. after practice change analysis of the incidence of BPD, ROP and NEC during the 8-year period spanning this change. The transfusion rate fell from a high of 14.8% of admissions in 2007 to a low of 6.3% in 2011 ( p  < 0.001). Concordant with this reduction patients had a lower incidence of; BPD (from 3.2% to 0.9%; OR, 3.722; CI 1.897–7.302), ROP (from 4.6% to 2.4%; OR 1.958, CI 1.247–3.073), and a trend toward less NEC (from 0.7% to 0.2%; OR 3.090, CI 0.835–11.443).